POSITION OF THE DIGITAL EVIDENCE BASED ON ARTICLE 184 & 185 CRIMINAL PROCEDURE CODE IN CYBER CRIMINAL INVESTIGATION IN THE COURT - Arie Febrianto (Faculty of Law, Universitas Sebelas Maret, 2017)
Law made by government and cooperation with legislator to establish order and regularity also peace in public .Basically every law made by legislators is the answer to the question of public law at the time of the establishment of the law. The legal developments must be in line with the development of society, so that when people change or grow then the law should be changed to arrange all the developments taking place in an orderly manner in the growth of modern society, because globalization has been the driver of the birth of the Information Technology era. In cyber crime cases, knowing the position of digital evidence in cases of cyber crime. The theory used in this research is a progressive legal theory with empirical juridical methods using qualitative data analysis, kind of his research is a descriptive study. The conclusion of this study, System proofs and evidences under Article 184 and 185 Criminal Procedure Code evidence of unconventional tools such as witness testimony and expert witnesses, as well as letters and instructions shift from conventional towards electronic will be able to ensnare cybercriminals. Law No. 11 of 2008 on Information and Electronic Transactions on Article 5 has been clearly stated that electronic information is a valid legal evidence in the form of electronic information and / or electronic documents and / or printout.